Leptospirosis and its prevention: knowledge, attitude and practice of urban community in Selangor, Malaysia - Abdullah, Nurul Munirah; Wan Mohammad, Wan Mohd Zahiruddin; Shafei, Mohd Nazri; Sukeri, Surianti; Idris, Zawaha; Arifin, Wan Nor; Nozmi, Noramira; Saudi, Siti Nor Sakinah; Samsudin, Suhailah; Zainudin, Abdul-Wahab; Awang Hamat, Rukman; Ibrahim, Rosni; et al. (BioMed Central, 2019)
Background: Leptospirosis is still endemic in Malaysia and has been prevalent in Selangor where cases have been underreported. Primarily, this was due to lack of awareness in the urban community in this region. This study determined the knowledge, attitude and preventive practice (KAP) of leptospirosis, and identified the significant predictors influencing KAP among urban community in Hulu Langat, Selangor. Methods: This cross-sectional study was conducted from 2015 to 2017 using validated questionnaire. Sampling methods included multistage cluster sampling, followed by simple random sampling to obtain 315 respondents. Descriptive analysis was performed to determine the KAP while χ 2 and the subsequent logistic regression analysis were carried out to identify associations and predictors between variables. Results: Respondents were mainly Malaysian Bumiputra with a mean (Standard Deviation (SD)) age of 32.5 (13.0) years. Of 315 respondents, 80.3% (n = 253) had poor knowledge, 87.0% (n = 274) had good attitude, and 81.3% (n =256) showed unacceptable practice towards leptospirosis and its prevention. Regression analysis identified age as the sole predictor influencing good knowledge (AOR 2.388; 95% CI = 1.298, 4.396; p = 0.005). Education level (AOR 2. 197; 95% CI = 1.109, 4.352; p = 0.024) was also noted as the significant predictor influencing the overall practice. Conclusions: The urban community in Selangor showed a positive attitude in waste management despite having little knowledge regarding the disease itself. The study also discovered inadequacy in preventive practice, hence marking the importance of the proper integration of knowledge and attitude into forming an acceptable practice to reduce transmission of Leptospira among urban population in Malaysia.